PHYSIOCHEMICAL QUALITY OF RAW MILK SAMPLES IN ANDHRA PRADESH - Cherryl, D.M; KALYANA CHAKRAVARTHI, M.; Ravindra Reddy, Y.; Indira, D. (Indian Journal of Animal Production and Management, 2017)
One hundred raw milk samples were collected randomly from 4 different villages ofProddatur mandal of Kadapa District in Andhra Pradesh to determine the physio – chemicalproperties. The organoleptic quality was conducted by a panel of experts as per standardscore card and the chemical constituents were determined by EKOMILK – Ultra PRO milkanalyzer. The results revealed that the milk samples from Kamanur village were slightlyhigher in fat, protein and solids not fat contents when compared with the rest of the other three villages